Cover Picture: Catalysts Based on Earth‐Abundant Metals for Visible Light‐Driven Water Oxidation Reaction (Chem. Rec. 11/2018). Issue 11 (19th November 2018) - Lin, Junqi; Han, Qing; Ding, Yong
Abstract : The cover picture shows visible light‐driven water oxidation catalyzed by three major kinds of catalysts based on earth‐abundant metals: all‐inorganic polyoxometalates, transition metal oxides and metal complexes containing multidentate ligand scaffolds. See the Personal Account by Y. Ding et al. (DOI:10.1002/tcr.201800029 ).